Insight into biological activities of chemically characterized extract from Marrubium vulgare L. in vitro, in vivo and in silico approaches - Gourich, Aman Allah; Touijer, Hanane; Drioiche, Aziz; Asbabou, Ayoub; Remok, Firdaous; Saidi, Soukaina; Siddique, Farhan; Ailli, Atika; Bourhia, Mohammed; Salamatullah, Ahmad Mohammad; Ouahmane, Lahcen; Mouradi, Aicha; et al. (Frontiers in Chemistry, 2023)
Aqueous extracts of Marrubium vulgare L. (M. vulgare) are widely used in traditional medicine for their therapeutic effects. Hence, this study aims to evaluate in vitro, in vivo, and in silico the biological activities of M. vulgare aqueous extract to further support their traditional use. Qualitative phytochemical tests of M. vulgare extracts showed the presence of primary and secondary metabolites, while quantitative analyses recorded revealed the contents of total phenols, flavonoids, and tannins, with values of 488.432 ± 7.825 mg/EAG gallic acid extract/g, 25.5326 ± 1.317 mg/EQ Quercetin extract/g and 23.966 ± 0.187 mg/EC catechin extract/g, respectively. Characterization of the phytochemical constituents of the extract revealed the presence of catechin and maleic acid as the most abundant while the evaluation of the antioxidant power revealed that the extract possesses significant antioxidant capacity, antimitotic potential, and antimicrobial properties against Streptococcus agalactiae and Staphylococcus epidermidis among many others. The antidiabetic activity of the extract showed a potent antihyperglycemic effect and a significant modulation of the pancreatic α-amylase activity as revealed by both in vitro and in vivo analysis, while an in silico evaluation showed that chemicals in the studied extract exhibited the aforementioned activities by targeting 1XO2 antimitotic protein, W93 antidiabetic protein and 1AJ6 antimicrobial protein, which revealed them as worthy of exploration in drug discovery odyssey. Conclusively, the result of this study demonstrates the numerous biological activities of M. vulgare and gives credence to their folkloric and traditional usage.